Empowering SMEs: Implementing Generative AI for Enhanced Copywriting in Bantul's Kusuka Ubiku - Syaifuddin, Akhmad; A'yun, Luthfia Qurrota (Society : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (SMEs) play a critical role in bolstering Indonesia’s economy. Efficient business management in these business typically encompasses four main areas: Human Resources, Operations, Marketing, and Finance. In Bantul, the SMEs within the Kusuka Ubiku community face significant challenges in effective marketing due to limited resources and expertise in copywriting. To address this, our program offers assistance in implementing generative AI technology to enhance copywriting skills. The initiative is structured in three phases: 1) Problem Identification, where the specific marketing hurdles are assessed; 2)  Assistance in Developing a Copywriting, which involves practical sessions on using generative AI tools; and 3) Evaluation and Feedback, to measure improvements in marketing outreach and effectiveness. The outcome of this assistance is a set of SMEs equipped with advanced copywriting tools and techniques, enabling them to produce market-relevant copywriting, expand their reach, and enhance brand recognition. The initiative not only aims to provide technical skills but also seeks to foster innovation, ultimately contributing to the sustainable growth of local businesses. Through this program, we anticipate a transformative impact on the marketing capabilities of SMEs in the region.